Aplicación de minicomputadoras - Portilla Robertson, Marcial; Segovia, Raymundo; Grijalva López, Manuel (My University, 1977)
Because dectapes are organized like disks, they are programmed in much the same fashion. Thus, before one can write in a specified block, the block must be located. A typical method to locate a block is to initiate tape motion and then search for the desired block in either the forward or reverse direction. the search consists of examining each block number as it is read and comparing it to the block number being sought. As soon as a match occurs, reading or writing to the located block may begin.
Keywords: circuitos lógicos; arquitectura de minicomputadoras; memoria; interfases; sistema operativo